Discovery of antivirulence agents against methicillin-resistant Staphylococcus aureus - Khodaverdian, Varandt; Pesho, Michelle; Truitt, Barbara; Bollinger, Lucy; Patel, Parita; Nithianantham, Stanley; Yu, Guanping; Delaney, Elizabeth; Jankowsky, Eckhard; Shoham, Menachem (Antimicrobial agents and chemotherapy, 2013)
Antivirulence agents inhibit the production of disease-causing virulence factors but are neither bacteriostatic nor bactericidal. Antivirulence agents against methicillin-resistant Staphylococcus aureus (MRSA) strain USA300, the most widespread community-associated MRSA strain in the United States, were discovered by virtual screening against the response regulator AgrA, which acts as a transcription factor for the expression of several of the most prominent S. aureus toxins and virulence factors involved in pathogenesis. Virtual screening was followed by similarity searches in the databases of commercial vendors. The small-molecule compounds discovered inhibit the production of the toxins alpha-hemolysin and phenol-soluble modulin α in a dose-dependent manner without inhibiting bacterial growth. These antivirulence agents are small-molecule biaryl compounds in which the aromatic rings either are fused or are separated by a short linker. One of these compounds is the FDA-approved nonsteroidal anti-inflammatory drug diflunisal. This represents a new use for an old drug. Antivirulence agents might be useful in prophylaxis and as adjuvants in antibiotic therapy for MRSA infections.